Prespektif Islam Mengenai Tradisi Manganan di Punden Mbah Rahmad Desa Gelang Kabupaten Jepara - Muhammad Nur Khabib; Ashif Az Zafi (Fakultas Adab dan Humaniora UIN Raden Fatah, 2020)
The tradition of Manganan or also called Nyadran is a tradition that is still preserved and preserved until now by village community Bracelet, subdistrict keling, District Jepara. It is usually performed during the Earth's charity celebrations. This research uses qualitative description methods. The results of the interviews, as well as the study of libraries are then analyzed using qualitative methods of descriptive analysis. The results of this study explained that 1) the implementation of the tradition Manganan in Punden Mbah Rahmad aims as a media grateful to Allah for the abundance of the earth and as a prayer to be kept away from calamities and diseases 2) symbols and the meaning of the tradition of Manganan consisting of lined leaves that contain the meaning of the ordinance of Prayer in congregation, rice and side dishes , the white porridge represents the origin of a child, frankincense which contains the meaning of one's means to pray, 3) concerning the perspective of Islam to the tradition of Manganan, can be attributed to the rule of Imam Syafi'i who mentions that appreciate the idea that grows and made role model among the community is better, than to difference the Sunnah that still Ikhtilah.